Anti-Leishmania major activity of Calotropis procera extract by increasing ROS production and upregulating TNF-α, IFN-γ and iNOS mRNA expression under in vitro conditions - Shahla Amani; Soheila Alinejad; Negar Asadi; Elham Yousefi; Shahram Khademvatan; Gordon Stanley Howarth (Tropical Medicine and Health, 2024)
Abstract Background Leishmaniasis, caused by protozoan parasites of the genus Leishmania, is a neglected tropical disease with 700,000 to 1,000,000 global new cases annually. Adverse effects associated with expense, long-term treatment and drug resistance have made conventional therapies unfavorable, encouraging the search for alternative drugs based on plant products. In this study, the effect of Calotropis procera (Asclepiadaceae) extract against viability of promastigotes and amastigotes of Leishmania major was evaluated in vitro. Methods The extract from the leaves of C. procera seedlings was prepared using a methanol maceration method. The colorimetric cell viability 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay was used to determine the growth-inhibitory effect of the extract on promastigotes. The level of reactive oxygen species (ROS) in promastigote cultures was determined after treatment with the extract using the 2',7'-dichlorofluorescein diacetate (DCFH-DA) method and compared with untreated cultures (control). After exposure to the extract the expression levels of tumor necrosis factor-α (TNF-α), interferon gamma (IFN-γ) and inducible nitric oxide synthase (iNOS) genes were determined and compared to control in peripheral blood mononuclear cells (PBMCs) infected with L. major. Results Based on the MTT assay, the C. procera extract significantly reduced the proliferation of L. major promastigotes with IC50 values of 377.28 and 222.44 μg/mL for 24 and 72 h, respectively (p < 0.01). After treatment with 222.44 and 377.28 μg/mL of C. procera extract, ROS production in L. major promastigote cultures increased 1.2- to 1.65-fold and 2- to 4-fold compared to the control, respectively (p < 0.05). C. procera extract induced significant increases in gene expression of TNF-α (2.76–14.83 fold), IFN-γ (25.63–threefold) and iNOS (16.32–3.97 fold) in infected PBMCs compared to control (p < 0.01). Conclusions On the basis of its anti-leishmanial activity, C. procera can be ...